PENGARUH LATIHAN FISIK TERSTRUKTUR TERHADAP PENURUNAN KADAR KOLESTROL PADA PASIEN HIPERTENSI DI RS GRANDMED LUBUK PAKAM - Miftahul Zannah; Tati Murni Karo-karo; Ida Yolanda; Rosita Ginting; Abdi Lestari Sitepu (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2021)
Hypertension and elevated cholesterol are two continuous conditions. Cholesterol level in the body is one of the most important factors to determine a person's risk of suffering from heart artery disease. Therefor it is necessary to provide Structured Physical Exercise in the form of regular exercise, in addition to reducing stress, it can also lose weight, burn more fat in the blood, and strengthen the heart muscle. To be able to do light exercise, you don't need to come to a special training ground, because the best program is one that you enjoy and can take place regularly. Methods: This study used a quantitative experimental method using post-test design with a control group (pretest-posttest with control group) with a sample size of 15 people. Sampling was used with purposive sampling technique using the Isac and Mikael formulas, the study was used in April 2021. Results: From the research results found in the experimental group the p value was 0.000 â‰¤ 0.05 and in the control group the p value was 0.001 â‰¤ 0.05. So it can be concluded that the experimental group gives a better effect than the control group on hypertension patients at Grandmed Lubuk Pakam Hospital in 2021. Therefor it is hoped that nurses at Grandmed Lubuk Pakam Hospital can improve services in non-pharmacological fields, especially for hypertension patients who suffering from hypercholesterolemia which can be overcome by giving intervention in the form of structured physical exercise.